Produksi benih ikan Lele Mutiara (Clarias Gariepinus Burchell, 1822) melalui pemijahan buatan pada unit pembenihan Ikan Unggul Farm - Nur Asiah; Henny Syawal; Eni Yulinda; Yuliati Yuliati; Yetti Elfina S (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The purpose of this community service activity is to transfer knowledge and technology about artificial spawning of pearl catfish (Clariasgariepinus Burchell, 1822) to the Unggul Farm fish hatchery unit in PangkalanBaru Village, Kec. Siak Hulu District. Kampar. This activity was carried out on July 12 - August 12, 2021. The results of the evaluation carried out by giving a pretest and post test showed that of the 10 (ten) participants who took part there was a comparison that before carrying out the service activities applying artificial fish spawning was still low. However, after participating in the activity, participants were able to understand about artificial catfish hatchery. The method is direct demonstration and active participation in applying artificial spawning technology, namely the process of removing eggs and sperm by stripping and surgery, so that eggs and sperm are obtained in maximum numbers. Artificial spawning results produce 20,000 larvae or a number of 3 tanks with a size of 5.5 X1 X 0.5 m. Natural spawning is carried out by the Unggul Farm fish hatchery unit each spawning period producing 5000 larvae in a 5.5 X1 X 0.5 m container. The benefits of artificial spawning are to increase the production of pearl catfish seeds and improve the welfare of members of the Unggul Farm fish hatchery unit.